Autophagy-mediated nanomaterials for tumor therapy - Liao, Zijian; Liu, Xiyu; Fan, Dianfa; Sun, Xingjun; Zhang, Zhikun; Wu, Pan (Frontiers in Oncology, 2023)
Autophagy is a lysosomal self-degradation pathway that plays an important protective role in maintaining intracellular environment. Deregulation of autophagy is related to several diseases, including cancer, infection, neurodegeneration, aging, and heart disease. In this review, we will summarize recent advances in autophagy-mediated nanomaterials for tumor therapy. Firstly, the autophagy signaling pathway for tumor therapy will be reviewed, including oxidative stress, mammalian target of rapamycin (mTOR) signaling and autophagy-associated genes pathway.Based on that, many autophagy-mediated nanomaterials have been developed and applied in tumor therapy. According to the different structure of nanomaterials, we will review and evaluate these autophagy-mediated nanomaterials'therapeutic efficacy and potential clinical application.